Direct numerical simulation of strongly heated air flows in a vertical pipe using a thermophysical property table. (September 2018) - Zhao, Pinghui; Liu, Jiaming; Ge, Zhihao; Li, Yuanjie; Zhao, Nian; Wan, Yuanxi
Highlights: DNS of strongly heated air flow was conducted with thermophysical property tables. Predicted velocity and temperature have an excellent agreement with experiment. Flow acceleration is the major cause of turbulence attenuation in such flow. FIK decomposition was applied to skin friction coefficient and Nusselt number. Quadrant analyses of Reynolds shear stress and turbulent heat flux are performed. Abstract: Direct numerical simulation using a thermophysical property table was conducted to study the characteristics of strongly heated air flows and heat transfer. The predicted mean velocity and wall temperature have an excellent agreement with the experimental data. Using a new scaling method, both the dimensionless velocity and temperature profiles show the trend of the laminarization due to the flow acceleration induced by strong heating. Effect of the Jensen inequality on mean properties can be neglected in this turbulent flow. The analysis of turbulent statistics shows that the flow acceleration is the major cause of turbulence attenuation in the strongly heated air flow. Also the buoyancy against flow direction has a suppressive contribution to the turbulence and heat transfer. The decomposition of the skin friction and Nusselt number illustrates that the turbulent contribution to the skin friction persistently decreases and laminar contribution increases along the streamwise direction, while the laminar contribution to the Nusselt number is dominant except in the entrance where the inhomogeneous contribution is dominant due to the quick development of the thermal boundary layer. The quadrant analysis shows that the events of sweep (cold fluids moving towards the wall) and ejection (hot fluids moving away from the wall) dominate the turbulent statistics. The coherent structures are persistently decreasing and slowly moving away from the wall along the streamwise direction due to the flow acceleration and buoyancy. Moreover, the predicted instantaneous coherent structures based on Q-criterion and streamwise vorticity also confirm that conclusion.